High speed, low jitter CMOS analog PLL for clock recovery application - Sudhaleswar Behera. (2008)
This thesis presents a CMOS PLL differential design techniques for whole PLL systems in order to reject supply-coupled noise. Apart from the supply coupled noise, there are other issues in the PLL systems such as closed loop bandwidth requirements, reduction of the VCO phase noise through appropriate topologies, dead zone elimination in PFD and reduction of charge sharing and clock feed through in Charge Pump. This thesis discusses all the issues briefly and applies same methodologies to the above design. Moreover, since this PLL uses differential structure, and hence works at reduced voltage swing, it is not only has the potential of operating at high frequency but also dissipate less power.